Assessment of Quality of life among patients with hip osteoarthritis - Usman Iftikhar, Farooq Islam, Gulraiz Enderyas, Faisal Shahbaz, Asim Raza, Sobia Azam, Haroon Arshad, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess quality of life in patients with hip osteoarthritis. Method: A hospital based cross sectional study was carried out involving hip osteoarthritic patients at District headquarter hospital Gujranwala. From May 2022 to Sep 2022.A total of 196 participants were included in the study. Data were collected from the patients who met the inclusion/exclusion criteria and were entered and analyzed in (SPSS) software version 24.36-Item (SF-36) was used to collect data from participants. Results: The results of the study showed that overall poor quality of life with mean scores physical functioning mean and standard deviationwas 31.13±9.73, role limitations due to physical health mean and standard deviation was 29.33±8.98, role limitations due to emotional problems mean and standard deviation was 22.60±9.31, energy/fatigue mean and standard deviation was 39.51±14.55, general health mean and standard deviation was 17.47±7.35. The goal of the study was to discover the effect of osteoarthritis on standard of living as well as their relationship with eight subscales of sf-36 as many people are not aware about their developed disease and my study will provide information regarding this disease in future. Conclusion: According to the findings of the study, Quality of life is significantly poor in hip osteoarthritis patients. Physical functioning, Role limitations due to physical health, General healthwere the most affected SF-36 subgroups. Keywords: Quality of life, Hip osteoarthritis, SF-36 Survey, Health related quality of life, rotational acetabular osteotomy